OutlierFlag: A Tool for Scientific Data Quality Control by Outlier Data Flagging - Shuai Huang; Yaqiang Wang; Yuanli Xie; Peng Zhao; Johannes Lüers (Journal of Open Research Software, 2016)
Scientific datasets collected by instruments usually include outliers which have to be flagged in data quality control process. OutlierFlag was developed to make this process accurate and simple by providing a suitable outlier data flagging algorithm and a user friendly GUI. The algorithm consists of three steps performed one by one: limitation check, error check and standard deviation check. Several parameters are configurable so the algorithm can be used for various datasets. OutlierFlag is an open source software written in Java and the MeteoInfo library was used for data plotting function.